ERROR ANALYSIS ON STUDENTS’ ESSAY COMPOSITION: REFERENCE FOR CORRECTIVE FEEDBACKING MECHANISM - Sarasua, Rocky James (International Journal of Arts, Sciences and Education, 2021)
Error analysis can help teachers discover and analyze language learners’ mistakes, allowing for opportunities for growth and optimization of their language learning. Hence, this descriptive-qualitative study analyzed learners’ errors in their essay composition. Corder’s stages in error analysis was employed analyzing the errors committed by the fifteen participants from Special Program for Journalism. The results showed that the participants committed twenty types of errors which can be categorized into sentential level and word level errors. Incorrect subject-verb agreement, erroneous verb tense, flawed use of preposition were among the frequently erred grammar concepts in the participants’ essay composition, while inappropriate pronoun usage was the least error type committed among the participants. The errors committed by the participants are linked to their first language, carelessness, and lack of mastery in the target language. This scenario necessitates language teachers to rethink, restructure and recalibrate their strategies, and teaching methods towards mastery of these grammar concepts. The findings of this study imply that language teachers and curriculum designers can utilize them to create an intervention or a corrective feedback mechanism to address these grammatical learning gaps and assist students grasp the subject. Key Words: Error Analysis, Corrective Mechanism, Corder’s EA Stages, Sentential and Word Level Errors